Holoprosencephaly in Kabuki syndrome. Issue 3 (17th December 2019) - Daly, Tara; Roberts, Abra; Yang, Edward; Mochida, Ganeshwaran H.; Bodamer, Olaf
Abstract: Kabuki syndrome is a rare, multi‐systemic disorder of chromatin regulation due to mutations in either KMT2D or KDM6A that encode a H3K4 methyltransferase and an H3K27 demethylase, respectively. The associated clinical phenotype is a direct result of temporal and spatial changes in gene expression in various tissues including the brain. Although mild to moderate intellectual disability is frequently recognized in individuals with Kabuki syndrome, the identification of brain anomalies, mostly involving the hippocampus and related structures remains an exception. Recently, the first two cases with alobar holoprosencephaly and mutations in KMT2D have been reported in the medical literature. We identified a de novo, pathogenic KMT2D variant (c.6295C > T; p.R2099X) using trio whole‐exome sequencing in a 2‐year‐old female with lobar holoprosencephaly, microcephaly and cranio‐facial features of Kabuki syndrome. This report expands the spectrum of brain anomalies associated with Kabuki syndrome underscoring the important role of histone modification for early brain development.